Students’ understanding of the emergent processes of natural selection: the need for ontological conceptual change - McLure, Felicity; Won, Mihye; Treagust, David (Taylor & Francis, 2020)
The topic of natural selection presents challenges to high school students since it requires understanding of an emergent process, which is a missing schema for most students. Many interventions for teaching natural selection have limited effect in bringing about substantial ontological conceptual change. This study evaluates the effectiveness of a series of lessons to build understanding of natural selection as an emergent process. A conceptual change approach enabled students to develop explanations through their transfer of understanding when producing a series of student-generated representations, culminating in elaborated written explanations of evolutionary scenarios. This process was supported through small-group social construction of understanding, Socratic questioning in whole class discussions and teacher feedback. A quasi-experimental design was used to compare conceptual change in experimental and comparison grade 10 classes using pre/post tests and analysis of written explanations. Results showed significantly greater conceptual change in the experimental class than the comparison class in pre/post tests and adoption of many aspects of the scientific ontological model in written explanations. This approach may be further developed as a method for supporting high school students’ understanding of this difficult topic.